Islam - "Khan, Mahammad Shabbir." (New Delhi, 1989)
This book deals with the Mores of social control, the social codes and individual life and major social goals within the framework of Islam, one of the most fundamental religions of the world; a Muslim's relationship with his family; his relationship with his communities and his cosmopolitan attitude towards all individuals of different countries of the world.
Keywords: Islam India